Improvements in the utilization of calcium carbonate in promoting sustainability and environmental health - Comes, Jackson; Islamovic, Emir; Lizandara-Pueyo, Carlos; Seto, Jong (Frontiers in Chemistry, 2024)
Calcium carbonate (CaCO3) is an incredibly abundant mineral on Earth, with over 90% of it being found in the lithosphere. To address the CO2 crisis and combat ocean acidification, it is essential to produce more CaCO3 using various synthetic methods. Additionally, this approach can serve as a substitute for energy-intensive processes like cement production. By doing so, we have the potential to not only reverse the damage caused by climate change but also protect biological ecosystems and the overall environment. The key lies in maximizing the utilization of CaCO3 in various human activities, paving the way for a more sustainable future for our planet.